Assessing the Role of Social-Legal Instruments in Mitigating Ecological Inequality Across Rapidly Industrializing Areas Experiencing Growing Environmental Pressures - Ghufron Maksum; Hilda Adinta Wulandari; Trinkul Kalita (Green Social: International Journal of Law and Civil Affairs, 2024)
Industrialization, while often driving economic growth, has led to significant environmental degradation, particularly in marginalized communities. These populations, already vulnerable due to socio-economic and geographic factors, bear the brunt of the environmental harm caused by industrial activities. This study explores the role of social-legal instruments in mitigating ecological inequality, focusing on their ability to reduce environmental burdens and empower marginalized communities in industrializing regions. A mixed-methods approach was employed, combining environmental data mapping and legal framework assessment. The study found that social-legal interventions, including rights-based advocacy, legal aid, and community participation, significantly reduced ecological disparities. By improving access to legal resources and fostering active community engagement in environmental governance, these interventions empowered vulnerable populations to advocate for their environmental rights. Positive correlations were found between the implementation of robust legal frameworks and reductions in pollution exposure, highlighting the effectiveness of integrating environmental and social protections. However, the study also identified several barriers to the effective implementation of these instruments, including political resistance, resource limitations, and unequal access to legal support. These challenges hinder the full realization of social-legal frameworks' potential. The study concludes with recommendations for policymakers to strengthen social-legal instruments by incorporating social equity into environmental regulations and improving the resources available to marginalized communities. Further research is needed to assess the long-term impacts of social-legal interventions and their scalability to other industrializing regions, with an emphasis on enhancing both ecological and social outcomes.